PEMBERDAYAAN MASYARAKAT IBU BALITA DENGAN PNEUMONIA MELALUI PEMBERIAN MAKANAN TAMBAHAN (PMT) PENYULUHAN DI PUSKESMAS KOTA LAMONGAN - Mujayanto; Eny Sayuningsih; Nuning Marina Pengge; Erlyna Jayeng (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Aisyah Pringsewu, 2021)
ABSTRACT Pneumonia is a respiratory tract infection that affects the lung parenchyma, causing inflammation. It is characterized by high fever, chills, shortness of breath, rapid breathing, coughing and chest indrawing. Mothers play an important role in supporting efforts to overcome nutritional problems, especially in terms of family nutritional intake, starting from food preparation, selection of food ingredients, to food menus. Pneumonia taken under five has 2 categories, namely mild - moderate and severe. The classification of pneumonia under five above shows that the majority of pneumonia under five in the working area of ​​the Lamongan District Health Center includes mild to moderate pneumonia with a total of 42 children (97.7%). From 2013 - 2018 there was an increase from 1.3% to 1.84%. Meanwhile, in the Lamongan Regency, there are still many cases of preumonia in Balia. The objectives of this community service are: 1. To find out the Nutritional Status by conducting anthropometric measurements 2. To increase the ability of cadres by holding training for refreshing cadres on anthropometric measurements 3. To increase the knowledge of the facilitators of providing food for making PMT Extensions made from local food with demonstration method facilitator training . From the results of this activity, there was no difference between before and after supplementary feeding. It is known that 80% of toddlers are classified as normal, 16% of toddlers are classified as short, and 4% of toddlers are classified as very short. ABSTRAK Pneumonia adalah suatu penyakit infeksi saluran pernapasan yang mengenai parenkim paru sehingga terjadi peradangan. Yang ditandai dengan adanya demam tinggi, menggigil, sesak napas, napas cepat, batuk dan tarikan dinding dada ke dalam. Ibu memegang peranan penting dalam mendukung upaya mengatasi masalah gizi, terutama dalam hal asupan gizi keluarga, mulai dari penyiapan makanan, pemilihan bahan makanan, sampai menu makanan. Pneumonia balita yang diambil mempunyai 2 kategori antara lain ringan - sedang dan berat. Klasifikasi Pneumonia balita diatas menunjukan bahwa sebagian besar balita Pneumonia di wilayah kerja Puskesmas Kota Lamongan termasuk Pneumonia tingkat ringan - sedang dengan jumlah 42 balita (97,7%). Dari tahun 2013 - 2018 mengalami kenaikan dari 1,3% menjadi 1,84%. Sedangkan di daerah Kabupaten Lamongan penderita Preumonia balia masih banyak dijumpai. Tujuan dari pengabdian masyarakat ini adalah : 1. Untuk mengetahui Status Gizi dengan mengadakan pengukuran antropometri 2. Meningkatkan kemampuan kader dengan mengadakan pelatihan untuk refreshing kader tentang pengukuran antropometri 3. Meningkatkan pengetahuan fasilitator pemberian Makanan pembuatan PMT Penyuluhan berbahan dasar pangan lokal dengan pelatihan fasilitator metode demonstrasi. Dari hasil kegiatan ini, tidak terdapat perbedaan antara sebelum dan setelah pemberian makanan tambahan. Diketahui sebesar 80% balita tergolong normal, 16% balita tergolong pendek, dan 4% balita tergolong sangat pendek.